LITERATURE REVIEW: GROWING STUDENT CHARACTER EDUCATION BASED ON LOCAL WISDOM IN SCIENCE LEARNING - Setya, Dely Sara; Maslia, Nurhidayatul; Sasmitha, Hijrana Mega; Rusda, Rusda; Erika, Farah (PROGRES PENDIDIKAN, 2024)
Character education based on local wisdom is an effort to prevent the decline of ethical and moral values of the younger generation in the educational process. This literature review aims to discuss the cultivation of local wisdom-based student character education in science learning. The method used in this study is Narrative Literature Review (NLR). Data collection through the Science Direct and Google Scholar databases, articles that have been published from 2017 to April 2023. The results of the literature review that has been carried out show that, local wisdom-based student character education in science learning in schools can be instilled by integrating the potential of local wisdom with activities extracurriculars, practicum or group learning, local tourism model learning, learning that is done with games, as well as through interactions between students using local languages.